Beyond the continuum : the changing role of aid policy in protrac ted crises - Harmer, Adele; Macrae, Joanna, 1966-; Overseas Development Institute (London, England). Humanitarian Po licy Group (London : Overseas Development Institute, 2004)
Includes statistical data.
Cover title.
"Researched, written, and published by the Humanitarian Policy Group at ODI."
Summaries of individual chapters in HPG research briefings nos. 16 & 17.
Includes bibliographical references (p. 71-75).
Keywords: United Nations; Disaster relief; Humanitarian assistance; Humanitarian assistance -- Government policy -- United States